A dual-label time-resolved fluorescence immunoassay for the simultaneous determination of cystatin C and β2-microglobulin in urine. Issue 4 (2nd October 2017) - Liu, Y; Liu, YH; Bei, WJ; Wang, K; Cui, TT; Li, HL; Wu, DX; Chen, SQ; Tan, N; Chen, JY
Abstract: Background : Contrast media is widely used in clinical diagnostic and interventional procedures, but may cause damage to the kidney, that is, contrast-induced nephropathy. This study was to establish a dual-label time-resolved fluorescence immunoassay (TRFIA) for the simultaneous determination of renal function markers cystatin-C (Cys-C) and β2 -microglobulin (β2 -MG) for the early diagnosis and follow-up surveillance of contrast-induced nephropathy. Methods : A sandwich immunoassay was used to detect the concentration of Cys-C, and the competitive immunoassay was used to detect the concentration of β2 -MG in 50 samples of urine. The performance of this dual-label TRFIA was evaluated and compared with commercial assays. Results : The sensitivity for Cys-C detection was 1.26 ng/ml, the average recovery was 99.36%; The sensitivity for β2 -MG detection was 2.13 ng/ml, the average recovery was 100.18%. Bland–Altman analysis showed that the dual-label TRFIA method and the commercial kits had a good agreement, suggesting they can be used interchangeably in clinical urine analysis. Conclusion : The present dual-label TRFIA has high sensitivity, specificity and accuracy in clinical sample analysis. This method can be used for the early diagnosis and follow-up surveillance of the contrast-induced nephropathy.